Evaluation of Net Energy, Standardized Ileal Digestible Lysine, and Soybean Meal Content Interactions in Pigs from 25 to 50 lb Using a Factorial Arrangement - Hilario M. Cordoba; Mike D. Tokach; Jason C. Woodworth; Katelyn N. Gaffield; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt; Henrique S. Cemin; Jose A. Soto (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 4,336 pigs (PIC 337 × 1050; initially 23.4 ± 0.70 lb) were used in a 21-d trial to investigate the interaction of NE, SID lysine, and soybean meal content on growth performance of nursery pigs. Pigs were housed in mixed-sex pens with 34 pigs per pen and assigned in a randomized complete block design to 16 dietary treatments arranged in a 2 × 2 × 4 factorial with eight replications per treatment. The treatment structure consisted of two levels of NE: 1,100 or 1,214 kcal/lb; two levels of SBM: 25.5 or 33.5%; and four levels of SID Lys: 1.08, 1.20, 1.31, or 1.43%. Eight diets were formulated to various levels of NE, SID Lys, and SBM and blended to create the 16 dietary treatments. Diets were corn-soybean meal-based, and soy hulls and soybean oil were added to modify the NE content of the diet. Feed-grade amino acids and SBM were used to adjust SID Lys and SBM content, respectively, and to maintain SID threonine, tryptophan, methionine, valine, and isoleucine ratios relative to SID Lys. There was a tendency for a three-way interaction (P = 0.063) in ADG between the NE, SBM, and SID Lys levels driven by the linear increase (P < 0.001) in ADG as SID Lys increased in diets containing 1,214 kcal NE/lb and 33.5% SBM, whereas the response to SID Lys at lower NE or SBM increased up to 1.20% with no improvement thereafter. For F/G, there was a three-way interaction (linear, P = 0.023) between the NE, SBM, and SID Lys levels driven by the improvement (linear, P < 0.001) in F/G at 1.08% SID Lys when NE was at 1,100 kcal/lb and SBM at 33.5% compared to the higher NE and lower SBM containing treatments. This response was likely caused by the greater Lys to calorie ratio and non-essential amino acids provided in this diet compared to the other diets containing 1.08% SID Lys. In conclusion, ADG and F/G improved as SID Lys increased in the diet; however, the magnitude of response was influenced by the Lys-to-CP and Lys-to-calorie ratios used within the different NE and SBM inclusions. Feed cost and feed cost per lb of gain increased as the levels of NE, SBM, and SID Lys increased in the diet.
Keywords: growth performance; late nursery; lysine; net energy; soybean meal